Burnout and Associated Factors Among Health Care Workers in Singapore During the COVID-19 Pandemic - Tan, Benjamin Y.Q. (J Am Med Dir Assoc, 2020)
OBJECTIVES: The strain on health care systems due to the COVID-19 pandemic has led to increased psychological distress among health care workers (HCWs). As this global crisis continues with little signs of abatement, we examine burnout and associated factors among HCWs. DESIGN: Cross-sectional survey study. SETTING AND PARTICIPANTS: Doctors, nurses, allied health professionals, administrative, and support staff in 4 public hospitals and 1 primary care service in Singapore 3 months after COVID-19 was declared a global pandemic. METHODS: Study questionnaire captured demographic and workplace environment information and comprised 3 validated instruments, namely the Oldenburg Burnout Inventory (OLBI), Safety Attitudes Questionnaire (SAQ), and Hospital Anxiety and Depression Scale (HADS). Multivariate mixed model regression analyses were used to evaluate independent associations of mean OLBI-Disengagement and -Exhaustion scores. Further subgroup analysis was performed among redeployed HCWs. RESULTS: Among 11,286 invited HCWs, 3075 valid responses were received, giving an overall response rate of 27.2%. Mean OLBI scores were 2.38 and 2.50 for Disengagement and Exhaustion, respectively. Burnout thresholds in Disengagement and Exhaustion were met by 79.7% and 75.3% of respondents, respectively. On multivariate regression analysis, Chinese or Malay ethnicity, HADS anxiety or depression scores ≥8, shifts lasting ≥8 hours, and being redeployed were significantly associated with higher OLBI mean scores, whereas high SAQ scores were significantly associated with lower scores. Among redeployed HCWs, those redeployed to high-risk areas in a different facility (offsite) had lower burnout scores than those redeployed within their own work facility (onsite). A higher proportion of HCWs redeployed offsite assessed their training to be good or better compared with those redeployed onsite. CONCLUSIONS AND IMPLICATIONS: Every level of the health care workforce is susceptible to high levels of burnout during this pandemic. Modifiable workplace factors include adequate training, avoiding prolonged shifts ≥8 hours, and promoting safe working environments. Mitigating strategies should target every level of the health care workforce, including frontline and nonfrontline staff. Addressing and ameliorating burnout among HCWs should be a key priority for the sustainment of efforts to care for patients in the face of a prolonged pandemic.